Genetic variability among robusta coffee genotypes in the state of Minas Gerais - Silva, Felipe Lopes da; Baffa, David Carlos Ferreira; Rezende, Juliana Costa de; Oliveira, Antonio Carlos Baião de; Pereira, Antonio Alves; Cruz, Cosme Damião (Coffee Science - ISSN 1984-3909, 2015)
The characterization and study of genetic diversity between accessions of the germplasm bank contribute to increased efficiency in selecting parents to be used in a breeding program. Thus, the objective of this work was to evalute genetic divergence by means of multivariate procedures among 71 genotypes of Coffea canephora var. kouilouensis and 56 genotypes of Coffea canephora var. robusta of the Germplasm Bank of the breeding program of Empresa de Pesquisa Agropecuária de Minas Gerais (EPAMIG) in a partnership with Universidade Federal de Viçosa. Together with this work, it was also aimed to indicating higher and more divergent genotypes to be used in intrapopulation crossings aiming at exploring greater genetic variability within segregating families. In July 2009, two experiments involving the genotypes of C. canephora var. kouilouensis and two experiments involving the genotypes of C. canephora var. robusta were deployed at the Experimental Farm EPAMIG in Oratorios, Minas Gerais, in an experimental randomized complete block design with five replicates and experimental plots consisting of a plant. The study was based on an evaluation of six morpho-agronomic traits in July 2010 and 2011. The indication of superior genotypes was determined using the selection index based on the sum of rank. Intrapopulation crossings between higher and divergent genotypes were indicated for creating greater genetic variability to be used in the offspring aiming at increasing the probability of obtaining higher individuals.